Solution‐Processed Small‐Molecule Bulk Heterojunction Ambipolar Transistors. (27th November 2013) - Cheng, Shiau‐Shin; Huang, Peng‐Yi; Ramesh, Mohan; Chang, Hsiu‐Chieh; Chen, Li‐Ming; Yeh, Chia‐Ming; Fung, Chun‐Lin; Wu, Meng‐Chyi; Liu, Chung‐Chi; Kim, Choongik; Lin, Hong‐Cheu; Chen, Ming‐Chou; et al.
<x xml:space="preserve">Abstract</x> Solution‐processed small‐molecule bulk heterojunction (BHJ) ambipolar organic thin‐film transistors are fabricated based on a combination of [2‐phenylbenzo[d, d']thieno[3, 2‐b;4, 5‐b']dithiophene (P‐BTDT) : 2‐(4‐n‐octylphenyl)benzo[d, d']thieno[3, 2‐b;4, 5‐b']dithiophene (OP‐BTDT)] and C60. Treating high electrical performance vacuum‐deposited P‐BTDT organic semiconductors with a newly developed solution‐processed organic semiconductor material, OP‐BTDT, in an optimized ratio yields a solution‐processed p‐channel organic semiconductor blend with carrier mobility as high as 0.65 cm2 V−1 s−1. An optimized blending of P‐BTDT:OP‐BTDT with the n‐channel semiconductor, C60, results in a BHJ ambipolar transistor with balanced carrier mobilities for holes and electrons of 0.03 and 0.02 cm2 V−1 s−1, respectively. Furthermore, a complementary‐like inverter composed of two ambipolar thin‐film transistors is demonstrated, which achieves a gain of 115.